Mathematics Pocketbook for Understanding Plane and Solid Shapes: Buku Saku Matematika untuk Memahami Bentuk Datar dan Ruang - Jayanti , Resy Dwi; Nisak, Nur Maslikhatun (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Mathematics is often perceived as difficult by elementary students, particularly in topics involving multiple formulas such as plane and solid shapes. Specific Background: Limited variations in teaching methods and the absence of appealing learning media often hinder students’ understanding. Gap: Existing resources rarely integrate concise formulas, visual properties, contextual examples, and digital interactivity in a single portable medium. Aim: This study aims to develop a mathematics pocketbook that supports students in learning fundamental concepts of plane and solid shapes. Results: The product consists of 14 compact pages containing formulas, properties, example problems, and an online game accessed through a barcode. The pocketbook is designed using simple language to improve comprehension and engagement. Novelty: The integration of formula summaries, shape properties, and digital game-based reinforcement within a portable printed format provides a unique learning resource. Implications: This pocketbook has the potential to assist teachers in delivering materials more effectively and to help students strengthen conceptual understanding during independent study. Highlights• Comprehensive formulas and properties in a compact format• Integrated online game through barcode scanning• Designed to support independent learning Keywords: Pocketbook, Mathematics, Plane Shapes, Solid Shapes, Elementary Students